Kepuasan Wisatawan Ditinjau dari Fasilitas, Tarif dan Daya Tarik pada Obyek Wisata Umbul Pelem di Kabupaten Klaten - Arum Chairunnisa; Fithri Marwanti; Eny Kustiyah; Istiqomah (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the impact of facilities, rates, and attractions on the level of tourist satisfaction visiting Umbul Pelem in Klaten. The study was conducted at Jl. Raya Tegalgondo-Pulon No. 88, Dukuh, Wunut, Klaten, Central Java. The research approach used is a descriptive quantitative method, with data collected through questionnaires. The study population includes all tourists who have visited Umbul Pelem Klaten. The sampling technique applied is incidental sampling, with a total of 100 respondents selected randomly, all of whom have visited at least twice. Data collection was carried out using questionnaires, which were then analyzed through various methods, including Instrument Validity and Reliability Test, Classical Assumption Test, Determination Coefficient Test, Multiple Linear Regression Analysis, F Test, Hypothesis Test, and R² Test using the SPSS 24 software. The results of the study reveal that facilities, rates, and attractions have a significant and positive influence on tourist satisfaction at Umbul Pelem Klaten. Overall, these three variables contribute 79.5% to tourist satisfaction, while the remaining 19.9% is influenced by other factors not included in this study, such as accessibility, promotional strategies, information, and other aspects. Keywords : Tourist Satisfaction, Facilities, Tariffs, Attractions